Posthuman Conjectures: Animal and Ecological Sciences in Marie Darrieussecq’s Dystopian Fiction - Posthumus, Stephanie (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2020)
Despite being published over twenty years apart, Marie Darrieussecq’s novels, Truismes (1996) and Notre vie dans les forêts (2017), share many features including their dystopian setting, urgent narrative tone, and themes of hybridity, corporeality and radical revelation. Deconstructing the boundaries between animal and human, nature and culture, human and machine, they invite the reader to move beyond anthropocentrism. In response to this invitation, I propose four posthuman conjectures, tracing the ethos of animal and ecological sciences in the two novels. First, I examine the ways in which the presence of non-human animal worlds requires imagining new subjectivities and writing embodied languages. Second, I move from the animal world to the machine cyborg who remains caught in the effects and affects of the techno-scientific complex in Darrieussecq’s dystopian fiction. Third, I consider the space made in both novels for death and dying as a non-metaphysical phenomenon situating humans in an eco-evolutionary web. Last, I define writing as a form of (post)human technology that the novels use to reject the notion of human superiority and to illustrate language’s capacity to imagine new, less-hierarchical paradigms.